Corporate culture and analyst catering - Pacelli, Joseph (Journal of Accounting and Economics, 2019)
This study examines the relation between financial institutions’ corporate culture and the quality of analysts’ research services. Using data collected from the Financial Industry Regulatory Authority, I measure the weakness of financial institutions’ corporate culture based on violations observed in securities activities unrelated to equity research. I find evidence demonstrating an association between weak corporate culture and analysts’ providing research products catered to institutional clients at the expense of individual investors. Specifically, FINRA violations are associated with both (i) less accurate forecasts and less informative reports, and (ii) higher institutional commission revenues and more broker-hosted conferences for select institutional clients.